THE IMPACT OF BEHAVIORAL RISK FACTORS ON INFERTILITY - Stamenković, Kristina (HEALTH CARE, 2025)
Behavioral factors are modifiable risk factors that can significantly influence the development of various health conditions and diseases. Literature suggests that these factors may also have a detrimental effect on fertility. The aim of this review paper was to present the contribution of behavioral factors to the development of infertility in both sexes through the analysis of scientific literature, and to propose preventive measures. The following databases were searched: MEDLINE, PubMed, and KOBSON. Subsequently, an analysis was conducted on the collected data from clinical and other epidemiological studies published over the past 30 years. Research findings indicate that diets rich in dietary fiber, omega-3 fatty acids, plant-based proteins, vitamins, and minerals positively influence fertility in both men and women. Conversely, diets high in processed foods, trans fats, and refined carbohydrates have been shown to have a negative impact on fertility. Moderate physical activity plays a critical role in maintaining an optimal body mass index and improving ovarian function. However, intensive physical activity, due to its effect on the hypothalamic-pituitary axis, can lead to hypothalamic amenorrhea and subsequent infertility. Smoking, alcohol abuse, and the use of psychoactive substances adversely affect fertility in both sexes, as well as fetal development. A balanced and healthy diet, moderate physical activity, prevention of sexually transmitted infections, and the design and implementation of targeted infertility prevention strategies can significantly improve fertility outcomes and contribute to safe motherhood.